Influence of product selection on health commodity security among level four public health facilities in Nairobi County, Kenya - Kaitany, Fridah C.; Mwangi, Eunice M.; Njoroge, Kezia (International Journal Of Community Medicine And Public Health, 2022)
Background: Procurement of health products and technologies in Kenya faces challenges as seen by increased public complaints regarding erratic supplies of the essential drugs and other medical supplies in public health facilities. Often overlooked, is the need to build effective product selection systems which can ensure there is availability of health commodities. Methods: The study adopted a cross sectional survey research design with descriptive approach involving 120 top management team, procurement officers, stores clerks, pharmaceutical officers and head of departments who were involved in procurement of health products and commodities from the 4 level four government health facilities in Nairobi County (Mbagathi Hospital, Pumwani Maternity Hospital, Mama Lucy Kibaki Hospital and Mutuini Hospital). The survey used questionnaires to collect data from the respondents. Consent was obtained from participantsabove the age of 18 years was included in to the study. Informed consent was taken prior to conduct of the study. Results: Correlation analysis indicated that product selection and health commodity security were positively correlated (r=0.769, p<0.05) while regression analysis indicated that product selection influenced health commodity security in level four public health facilities in Nairobi City County, Kenya (β=0.457; p=0.05). Conclusions: Product selection is important to ensure health commodity security. The management at the facilities should ensure product selection committees are available in the facilities, products selected are registered for use in the country and ensure that the user departments are involved in product selection.